Analisis determinan impor beras di Indonesia - Muhammad Rizky Mulya; Haryadi Haryadi; Rahma Nurjanah (e-Journal Perdagangan Industri dan Moneter, 2020)
This study aims to determine and analyze the development of a gross domestic product, population, rupiah exchange rate, inflation, and rice imports. In addition, to choose and investigate the effect of gross domestic product, people, rupiah exchange rate, inflation, and rice imports. The method used to analyze this research is descriptive quantitative. This study uses multiple linear regression analysis based on Ordinary Least Square (OLS). Based on the results of this study, the development of rice imports fluctuates every year. It tends to increase rice imports, gross domestic product fluctuates and tends to grow, the population increases every year, the rupiah exchange rate fluctuates, and inflation fluctuates every year and tends to decrease. The results of multiple linear regression show that the variables of gross domestic product, population, and exchange rate significantly affect rice imports in Indonesia. In contrast, the inflation variable is not substantial on rice imports in Indonesia. Keywords: Import rice, GDP, Total population, Exchange rate, Inflation.